2022
DOI: 10.3390/biology11020259
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of an Annexin-Related Prognostic Signature and Therapeutic Targets for Bladder Cancer: Integrative Analysis

Abstract: Abnormal expression and dysfunction of Annexins (ANXA1-11, 13) have been widely found in several types of cancer. However, the expression pattern and prognostic value of Annexins in bladder cancer (BC) are currently still unknown. In this study, survival analysis by our in-house OSblca web server revealed that high ANXA1/2/3/5/6 expression was significantly associated with poor overall survival (OS) in BC patients, while higher ANXA11 was associated with increased OS. Through Oncomine and GEPIA2 database analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Thus, it is essential to identify molecular markers to detect bladder cancer early before cancer cells become invasive and metastatic. Annexins display different expression patterns in bladder cancer and play an essential role in the pathogenesis by triggering various downstream signaling pathways and functional regulatory effects [ 19 , 20 , 43 , 44 , 45 , 46 , 47 , 48 ]. Increasing evidence indicates that AnxA2 is upregulated in several types of human cancer [ 13 , 17 , 21 , 22 , 24 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is essential to identify molecular markers to detect bladder cancer early before cancer cells become invasive and metastatic. Annexins display different expression patterns in bladder cancer and play an essential role in the pathogenesis by triggering various downstream signaling pathways and functional regulatory effects [ 19 , 20 , 43 , 44 , 45 , 46 , 47 , 48 ]. Increasing evidence indicates that AnxA2 is upregulated in several types of human cancer [ 13 , 17 , 21 , 22 , 24 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, ANXA3 has been found to not only maintain genomic integrity and facilitate cell proliferation and differentiation but also contributes to tumor initiation and growth. We synthesized the relevant literature and found that that ANXA3 expression was dysregulated in a large number of tumor populations, such as bladder urothelial carcinoma ( 23 ), BRCA ( 17 ), CHOL ( 16 ), COAD ( 24 ), esophageal carcinoma ( 25 ), head and neck squamous cell carcinoma ( 26 ), kidney chromophobe ( 27 ), kidney renal papillary cell carcinoma ( 28 ), hepatocellular carcinoma ( 29 ), LUAD ( 30 ), LUSC ( 31 ), pancreatic adenocarcinoma ( 32 ), PRAD ( 33 ), READ ( 34 ), stomach adenocarcinoma ( 25 ), thyroid carcinoma ( 35 ), and uterine corpus endometrial carcinoma ( 13 ). In this study, an increased ANXA3 expression was associated with a favorable prognosis, suggesting that ANXA3 might play a pivotal role in decreasing cancer risk in patients with OV.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, ANXA11 expression levels were decreased in tumor tissue compared to the normal counterpart, and together with other annexins, serves to identify luminal-subtype bladder tumors ( Wu et al, 2021 ). Moreover, high ANXA11 levels were associated with a higher overall survival in bladder cancer patients ( Yao et al, 2022 ), further supporting an oncosuppressor role in this malignancy.…”
Section: Annexin A11mentioning
confidence: 92%